Ethiopian residents' knowledge and attitude towards blood donation and its associated factors: systematic review and meta-analysis - Addisu Getie; Baye Tsegaye Amlak; Temesgen Ayenew; Mihretie Gedfew; Gizachew Yilak; Adam Wondmieneh; Melaku Bimerew (BMC, 2024)
Abstract Introduction Despite the existence of numerous blood donation centers globally, there remains a significant gap between the demand and supply of blood. In Ethiopia, replacement blood donation is more common than voluntary donation. The National Blood Bank of Ethiopia collects approximately 200,000 units of blood each year, while the daily requirement is 18,000 units. Donors' knowledge and attitudes are vital for ensuring a steady blood supply. This systematic review and meta-analysis sought to evaluate the knowledge and attitudes of Ethiopian residents regarding blood donation and the factors influencing them. Methods Relevant research articles were identified through searches of various databases. Data extraction and organization were performed using Microsoft Excel, and the data were then analyzed using STATA/MP 17.0. A weighted inverse variance random-effects model with a 95% confidence interval was employed to pool the data. Heterogeneity was examined with the Galbraith plot and Cochrane I² statistics. To identify sources of heterogeneity, meta-regression, subgroup analysis, and sensitivity analysis were conducted. Publication bias was assessed using Egger's test and managed with trim and fill analysis. The adjusted odds ratio was calculated to explore the relationship between knowledge and attitudes towards blood donation, with a significance threshold of p < 0.05. Results The pooled prevalence of favorable attitudes towards blood donation was 65.95%. Moderators such as study year (p = 0.72), publication year (p = 0.877), and sample size (p = 0.291) were not significant, indicating they did not contribute to heterogeneity. Studies from Northern Ethiopia reported the highest prevalence of favorable attitudes at 69.95%, while research on healthcare workers also indicated a high proportion of favorable attitudes at 69.29%. There was a significant association between knowledge and attitudes towards blood donation (AOR = 2.03). Conclusion The pooled prevalence of favorable attitudes towards blood donation was 65.95%, with the highest levels observed in Northern Ethiopia and among healthcare workers. A significant association between knowledge and positive attitudes towards blood donation was found. To enhance attitudes towards blood donation, increasing public awareness and education about the importance and safety of donating blood is crucial.